Ethics in Public Administration in Kosovo - Duraku, Azem (European Journal of Multidisciplinary Studies, 2018)
It is important for the state to maintain and increase public confidence in the Public Administration. This trust grows and is kept in public only when civil servants, officials, perform duties with integrity, impartiality and fairness. Ethics is being discussed very recently and it is becoming an extremely mention topic for the business, public administration and in social private environments. Unethical and corrupt behaviour can not only be prevented by punitive measures, from inside and outside analysis, it has a negative perception on corruption in state institutions. Every day in the media, we can encounter information about the bad behaviour of public administration officials regarding corruption, Kosovo is ranked in unsatisfactory positions regarding this phenomenon. It is important to prepare the self-public manual institution guide, which should rely on international standards and policy implementation in practice.The question is whether only legal and sublegal acts are enough to keep this problem under control ? In this paper we will study the legislation, covering the field of ethical behaviour and good practices of combating these negative phenomena.
Keywords: Ethics, The code of conduct, Integrity, Public officials, Public administration.